A Table for One A Critical Reading of Singlehood, Gender and Time - Lahad, Kinneret (Manchester University Press, 2017)
A Table for One explores the links between female singlehood and social time, juxtaposing two theoretical fields that are rarely linked: the social study of time and the study of singlehood. By adopting an interdisciplinary approach, this book paves the way for a new theorisation of singlehood which will put it at the fore of deconstructive critical thinking and on the feminist agenda. Although the rise in the number of single-women households has sparked a new wave of singlehood scholarship, the concept remains relatively under-theorised and under-incorporated into social and feminist research, and critical studies in general. Drawing on a wide variety of cultural resources - including web columns, blogs, expert advice columns, popular cliches, advertisements and references from television episodes - this book sketches the meaning-making processes of singlehood and time in Israel.